ASSESSING HOW GREEN CONTROLLING IMPLEMENTATION DRIVES CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION RESULTS: A QUANTITATIVE APPROACH - Ferinia Pintauli, Rolyana (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
This study attempts to determine how the implementation of green controlling can enhance the outcomes of Corporate Social Responsibility (CSR) initiatives among employees. This research employs a quantitative methodology with an explanatory framework to elucidate the impact of green controllable variables on the implementation of CSR. The sample comprised 164 employees from organizations that apply green controlling and CSR practices, selected via non-probability sampling methods. Data collection was conducted using a questionnaire utilizing a 5-point Likert scale, administered through Google Forms over a two-week period. The findings indicated that green controlling exerted a substantial and beneficial influence on the implementation of CSR. A robust sustainability control system can facilitate implementation tasks. This study's innovation is in recognizing that green controlling procedures serve not only for regulatory compliance but also provide organizations with chances to enhance profitability through corporate social responsibility (CSR).